Discursive representation of war in personal letters sent during the Malvinas War - Carrizo, Alicia (2023)
On April 2, 1982, the Malvinas War began, in which Argentina confronted the United Kingdom to recover the Malvinas Islands. It occurred within the framework of the last military dictatorship, so that the dictatorship and the war are intertwined in social memory (Guber, 2001; Lorenz, 2009). The objective is to study the discursive representation of the war in personal letters written on the battle front in order to make the voice of the soldiers visible. We focus, in particular, on the available meanings activated by the protagonists in relation to their participation in the conflict. The analysis of the texts takes systemic functional linguistics (Halliday, 1982, 1985) as a base theory. It also integrates the analysis of argumentation (Carrizo, 2012, 2019) and the structures of participation and interactional positioning (Goffman, 1974, 1981) from the perspective of strategic discourse analysis (Menéndez 2019), and critical discourse analysis (Fairclough, 2003; Pardo, 2008). Preliminary results show strategies that circumvent the differences between protagonists in pursuit of the shared experience that legitimizes participation.